2013
DOI: 10.1088/0034-4885/76/5/056401
|View full text |Cite
|
Sign up to set email alerts
|

Information physics fundamentals of nanophotonics

Abstract: Nanophotonics has been extensively studied with the aim of unveiling and exploiting light-matter interactions that occur at a scale below the diffraction limit of light, and recent progress made in experimental technologies--both in nanomaterial fabrication and characterization--is driving further advancements in the field. From the viewpoint of information, on the other hand, novel architectures, design and analysis principles, and even novel computing paradigms should be considered so that we can fully benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 165 publications
0
28
0
Order By: Relevance
“…More detailed modeling will be needed to fully explain this, for example, by including state filling effects which may occur in cases where the excitation power is high. 19 This will be one of the topics of future work.…”
Section: Stochstic Modelingmentioning
confidence: 97%
See 2 more Smart Citations
“…More detailed modeling will be needed to fully explain this, for example, by including state filling effects which may occur in cases where the excitation power is high. 19 This will be one of the topics of future work.…”
Section: Stochstic Modelingmentioning
confidence: 97%
“…19 We consider a quantum dot based on a semiconductor material with a bulk electric dipole moment, on which a lightwave with a specific resonance frequency is incident. For the electronic system confined in a quantum dot, the electronic wave operator includes an envelope function of electronic waves in the quantum dot.…”
Section: B Theoretical Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed treatment of the modeling can be found in [14]. Essentially, the same formulation is found in the research on environment-assisted quantum walks [26,27].…”
Section: Photoexcitation Transfer Modelingmentioning
confidence: 99%
“…In fact, Naruse et al theoretically and experimentally demonstrated that the versatile spatiotemporal dynamics induced in multiple-quantum-dot systems by optical near-field interactions can be used to solve CSP [9,14] and MAB [15,16]. Furthermore, Aono et al showed that the satisfiability problem (SAT), which is known to be one of the most important NP-complete problems, can be solved [14]. Naruse et al also demonstrated solving MAB by using single photons emitted from a nanodiamond [17].…”
Section: Introductionmentioning
confidence: 99%